Metastasizing Malignant Granular Cell Tumor (Abrikossoff Tumor) of the Anterior Abdominal Wall, with Prolonged Survival - Yara A. Alnashwan; Khaled A. H. Ali; Samir S. Amr (Hindawi Limited, 2019)
Malignant granular cell tumor (MGCT) is a rare high-grade mesenchymal tumor of Schwann cell origin. MGCTs commonly affect thigh, extremity, and trunk; however, involvement of the abdominal wall is quite rare. It has poor prognosis with 39% mortality rate in 3-year interval. We report a 50-year-old female who had MGCT arising in the anterior abdominal wall and developed massive metastatic deposits in both lungs and in the right inguinal lymph nodes, with prolonged survival for 11 years. A brief review of the literature is presented.